(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2012)
A rapid and sensitive spectrofluorimetric method was developed for the determination of amlodipine (AD), a calcium channel blocker, in the plasma. The type of solvent, the wavelength range, and the range of AD concentration were selected to optimize the experimental conditions. The calibration curves were linear (r² >;0.997) in the concentration range of 0.1-12.5 ppm of AD. The limit of quantitation and limit of detection values for the method for plasma samples were 0.1 ppm and 0.07 ppm, respectively. The precision calculated as the relative standard deviation was less than 3.5%, and the accuracy (relative error) was better than 5.5% (n=6). The method developed in this study can be directly and easily applied for the determination of AD in the plasma without derivatization in plasma.